When the social networks and internet come to the rescue of entrepreneurs: The problematic of crowdfunding in Africa - René Guy Omenguélé; Yimpi Cédric Mbouolang (The Journal of Entrepreneurial Finance (JEF), 2022)
Since 2007, crowdfunding platforms have abounded on the web. It is estimated at 2.5 billion dollars the potential of the crowdfunding market in sub-Saharan Africa by 2025. The objective of this paper is to make an inventory of Crowdfunding activities in Africa, region with a most restrictive access to bank loan by SMEs, start-ups and young entrepreneurs. It appears from the economic and socio-cultural realities that Africa is a region with more potential catalyst for crowdfunding industry takeoff. However, there are many factors which are presented in this study as potential inhibitors of African CF market competiveness. This study has identified digital divide as one of the main potential inhibitors of crowdfunding development in Africa. By waiting an empirical test of this proposition, local authorities may act to reduce any further the digital gap in their country in order to enhance crowdfunding industry takeoff in Africa.
Keywords: G15; G23; L26; O16; O35; 650; crowdfunding; digital divide; entrepreneurship; financing; Africa